2014
DOI: 10.1042/bj20140848
|View full text |Cite
|
Sign up to set email alerts
|

CYP-13A12 of the nematode Caenorhabditis elegans is a PUFA-epoxygenase involved in behavioural response to reoxygenation

Abstract: SHORT TITLE:CYP-13A12 of C. elegans is a PUFA-epoxygenase 4 SYNOPSISA specific behavioural response of Caenorhabditis elegans, the rapid increase of locomotion in response to anoxia/reoxygenation called the O2-ON response, has been used to model key aspects of ischemia/reperfusion injury. A genetic suppressor screen demonstrated a direct causal role of CYP-13A12 in this response and suggested that CYP-eicosanoids, which in mammals influence the contractility of cardiomyocytes and vascular smooth muscle cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Notably, it is not the decreased expression of cyp-25A1 and ugt-63 that contributes to anoxia sensitivity since the knockdown of these genes using RNAi actually enhanced anoxia survival. The ugt-63 and cyp-25A1 genes, part of gene Cluster 4 and 5 ( Figure 4, B and E ), code for proteins that show homology to detoxification system proteins ( Ma et al 2013 ; Keller et al 2014 ; Gems and McElwee 2005 ). The RNA-Seq data indicate that several ugt and cyp gene family members have a differential gene expression profile in the anoxia sensitive animals relative to controls ( Figure 4A and Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, it is not the decreased expression of cyp-25A1 and ugt-63 that contributes to anoxia sensitivity since the knockdown of these genes using RNAi actually enhanced anoxia survival. The ugt-63 and cyp-25A1 genes, part of gene Cluster 4 and 5 ( Figure 4, B and E ), code for proteins that show homology to detoxification system proteins ( Ma et al 2013 ; Keller et al 2014 ; Gems and McElwee 2005 ). The RNA-Seq data indicate that several ugt and cyp gene family members have a differential gene expression profile in the anoxia sensitive animals relative to controls ( Figure 4A and Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans , CYP-modified PUFA metabolites appear to regulate pharyngeal pumping, possibly through the activation of ion channels 22 23 . Recently, CYP-modified PUFAs, specifically 17,18- EEQ, was shown to impart protection against ischemic/reperfusion damage 9 35 . Thus, CYP-modified PUFA metabolites perform a range of important physiological functions in both vertebrates and invertebrates that are just beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Though strong evidence indicates that epoxide fatty acid metabolites act in signal transduction, no receptors for these molecules have been identified 38 39 . Recently discovered functions for specific eicosanoids in C. elegans , such as the requirement for F-series prostaglandins in sperm guidance 28 29 32 , CYP involvement in response to hypoxia and re-oxygenation 9 35 , and the sensitivity of germ cells to oxygenated metabolites of dietary DGLA, demonstrate the utility of the genetically amenable C. elegans system for the discovery and elucidation of cellular mechanisms of eicosanoid signaling in physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The C. elegans study showed that CYP-13A12 responds to the oxygen-dependent enzyme EGL-9 and hypoxia-inducible factor (HIF-1) to facilitate a movement response to reoxygenation after oxygen deprivation [ 86 ]. CYP-13A12 generates epoxy and hydroxyl eicosanoids from AA and EPA, including 14,15-epoxyeicosatrienoic acid (14,15-EET) from AA and 17,18-EEQ from EPA [ 88 ]. This research implicates conserved roles for omega-6 and omega-3 PUFAs and eicosanoid formation in ischemia and reperfusion.…”
Section: Functions Of Omega-6 and Omega-3 Fatty Acids In mentioning
confidence: 99%